Role of Plasmids in Beer Spoilage Lactic Acid Bacteria: A Review. (23rd November 2020) - Suzuki, Koji; Shinohara, Yuji; Kurniawan, Yohanes Novi
Abstract: Beer is a hostile environment for microorganisms to survive. However, some strains of lactic acid bacteria (LAB) have chosen this harsh environment for their ecological niche and evolved by incrementally acquiring various genetic elements to overcome a range of growth hurdles posed by beer. In fact, over 100 genes appear to be involved for one beer spoilage LAB strain to grow in and spoil beer. Although many of them are chromosomally encoded genes, an increasing number of brewery-specific genetic clusters have been also identified on plasmids, which are often horizontally shared by a variety of beer spoilage LAB species/strains. These plasmid-localized genetic factors were once represented by hop tolerance genes, such as horA, horC, and hitA, that were uncovered in the early days of hop tolerance research. But the recent evidence increasingly indicates that beer spoilage potential of LAB is conferred by multifactorial and complex adaptive responses that are related to a large number of defense mechanisms, including divalent cation homeostasis, cell envelope modification, oxidative stress response, and pH homeostasis. Many of these defense systems have been shown to be encoded on plasmids that are carried by beer spoilage LAB. In the past decade, new plasmid-encoded diagnostic marker genes (DMGs), such as gtfD15 and fabZ, have been additionally reported for the discrimination of beer spoilage potential of LAB strains. This review summarizes the recent progress in this area of research and provides some insights into the microbiological quality control (QC) tests adopted in brewery laboratories.